2017
DOI: 10.1016/j.celrep.2017.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Brachyury-YAP Regulatory Axis Drives Stemness and Growth in Cancer

Abstract: SUMMARY Molecular factors that define stem cell identity have recently emerged as oncogenic drivers. For instance, brachyury, a key developmental transcriptional factor, is also implicated in carcinogenesis, most notably of chordoma, through mechanisms that remain elusive. Here, we show that brachyury is a crucial regulator of stemness in chordoma and in more common aggressive cancers. Furthermore, this effect of brachyury is mediated by control of synthesis and stability of Yes-associated protein (YAP), a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 90 publications
0
54
1
1
Order By: Relevance
“…Yes-associated protein (YAP), an effector of the Hippo pathway and a master regulator of organ development (41), was recently found to be directly transactivated by BRACHYURY in chordoma cells through binding to the proximal region of the YAP promoter. Interestingly, BRACHYURY regulates YAP signaling through a non-transcriptional mechanism in lung carcinoma (18). Both BRACHYURY and YAP expressions were found to be elevated in glioblastoma and brain metastases originating from lung carcinomas, and BRACHYURY knockdown resulted in a significant decrease in YAP protein and mRNA expression in primary glioblastoma cells.…”
Section: Downstream Regulatory Network By Brachyury Activationmentioning
confidence: 99%
“…Yes-associated protein (YAP), an effector of the Hippo pathway and a master regulator of organ development (41), was recently found to be directly transactivated by BRACHYURY in chordoma cells through binding to the proximal region of the YAP promoter. Interestingly, BRACHYURY regulates YAP signaling through a non-transcriptional mechanism in lung carcinoma (18). Both BRACHYURY and YAP expressions were found to be elevated in glioblastoma and brain metastases originating from lung carcinomas, and BRACHYURY knockdown resulted in a significant decrease in YAP protein and mRNA expression in primary glioblastoma cells.…”
Section: Downstream Regulatory Network By Brachyury Activationmentioning
confidence: 99%
“…Instead, YAP/TAZ are often overexpressed and highly accumulated in the nuclei in cancer cells [ 107 , 109 ]. This phenotype is preserved in many cancer tissues [ 110 113 ]. Apparently, YAP/TAZ overexpression promotes transcription of YAP/TAZ target genes [ 114 , 115 ].…”
Section: Yap/taz In Cancermentioning
confidence: 99%
“…23 Recent studies indicate that VP is also a potent inhibitor of Yes-associated protein (YAP), a key transcriptional coactivator of the Hippo pathway and has been shown to operate as an oncoprotein in cancers. 24 With YAP being overactive in cancerous tissues, we postulated that VP could show cytotoxic effects to a greater degree on GBM cells in comparison to healthy brain stromal cells, 7,10,12,[25][26][27] as was previously shown for multiple cancers, including pancreatic, small cell lung cancer, triplenegative breast cancer, and brain cancer. 21,[28][29][30][31] In this study, we encapsulated VP in a micelle vehicle composed of poly(ethylene glycol)-poly(β-amino ester)poly(ethylene glycol) (PEG-PBAE-PEG) triblock copolymer.…”
Section: Introductionmentioning
confidence: 82%
“…6 Mechanical and chemical signaling promotes recurrence of the tumor and it is difficult to overcome the elaborate pathways and signals involved to attenuate further invasive growth of the tumor. [7][8][9][10][11][12] After resection, it has been suggested that the tumor cells undergo a shift to a more drug-resistant state, preventing commonly used chemotherapeutic drugs such as temozolomide (TMZ) from having a significant therapeutic effect. 13,14 Therefore, new therapeutics as well as new technologies able to deliver high drug doses to brain tumor cells are needed to provide long-term protection of the microenvironment and prevent tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%